Study of immunization status of under: five children in relation to various demographic variables of their mothers - Agarwal, Khushboo; Karnawat, Bhag Singh; Singh, Monika; Garg, Pukhraj; Jain, Anil Kumar; Singh, Kanwar (International Journal of Contemporary Pediatrics, 2019)
Background: Immunization remains an important public health intervention. On one side morbidity and mortality caused by vaccine-preventable diseases are still high in developing countries, on the other side immunization coverage is still low. Present study aims to assess immunization status of under-five children in relation to various demographic variables of their mothers. Methods: A total of 530 mothers with children under 5 years attending OPD, immunization clinic or admitted in paediatric ward were included in the study. Maternal demographic variables like age, religion, education, socio economic status, residence, parity and occupation were compared with immunization status of their children. Results: Most of mothers were housewives (73.77%), primary educated (33.58%), belonged to Hindu religion (47.54%), were of 21-30 years age group (52.64%), residing in urban areas (62.07%) and belonged to middle socio economic status (45.84%). Out of total 530 children 161 (30.37%) were completely immunized as compared to 21.32% who were unimmunized. Boys were marginally more unimmunized (37.32%) than girls (23.04%). Mothers’ education, occupation, parity, religion, residence and socio-economic status significantly influenced immunization status of their children (p<0.05). Conclusions: Therefore, it is recommended that any strategy formulated to improve vaccination coverage in children of our country should focus to strengthen above mentioned weak links.